Direct measurement of the effect of cold rolling on β phase precipitation kinetics in 5xxx series aluminum alloys. (15th January 2017) - Scotto D'Antuono, D.; Gaies, J.; Golumbfskie, W.; Taheri, M.L.
Abstract: The aluminum magnesium alloy system has notable attributes, such as a high strength to weight ratio and weldability, but it can become susceptible to sensitization at relatively low temperatures, which can lead to stress corrosion cracking. It is well established that growth of the secondary β phase is temperature driven, however there is little understanding about the role of prior strain in the β phase nucleation and growth process. Understanding the effect of cold rolling will also bring new insight into better thermomechanical treatments leading to a more appropriate temper to improve sensitization resistance. In this study cold rolled AA5456-H116 is observed during in situ transmission electron microscopy heating experiments. The results of this study show the impact of an increased dislocation density, due to cold rolling, on β phase precipitation as well as the effect of misorientation on growth and kinetics. The effect of additional dislocations is also observed to show an increase in precipitate density and a lowering of nucleation temperature attributed to Mg pipe diffusion. Graphical abstract: Image 1